Jews in the German economy : the German-Jewish economic élite 1820 - 1935 - Mosse, Werner E. 1918-2001 (Clarendon, 1987)
Werner E. Mosse: Jews in the German Economy. The German-Jewish Economic Elite 1820-1935. Clarendon Press, Oxford 1987. 420 Seiten, 35 Pfund